How might a collapse in the Atlantic Meridional Overturning Circulation affect rainfall over tropical South America?. Issue 1 (9th December 2021) - Good, Peter; Boers, Niklas; Boulton, Chris A.; Lowe, Jason A.; Richter, Ingo
Abstract: The seasonal response of rainfall over tropical South America to a shutdown in the Atlantic Meridional Overturning Circulation (AMOC) is examined, in HadGEM3 model simulations where freshwater is added to the north Atlantic. Potential biases in these simulations are explored by comparing the unperturbed simulation with observations. In this simulation, in years when the latitude of the model Atlantic Intertropical Convergence Zone (ITCZ) is realistic, the model provides a reasonable simulation of the spatial and seasonal variation in regional‐scale rainfall over tropical South America. However, some climatological mean rainfall biases over this region are attributed to the climatological southward bias in the Atlantic ITCZ. Under an AMOC shutdown, the rainfall changes over tropical South America are largely associated with a southward shift of the Atlantic ITCZ. The large seasonal variation in rainfall change over tropical South America is linked primarily with the variation in the location of peak rainfall (itself driven largely by variation in the latitude of peak solar insolation and by the lagged variation in Atlantic ITCZ). The simulated rainfall changes appear to be biased in some months by the southward bias in the Atlantic ITCZ, including a possible overestimation of drying in March and June. In addition, the Atlantic ITCZ in HadGEM3 tends to shift too far in both the seasonal cycle (as reported in other models) and in inter‐annual variability. Excessive inter‐annual variability may arise because the model ITCZ is too close to the equator, combined with an increase in variability near the equator. Further understanding of what drives the variability in ITCZ latitude, and how that relates to ITCZ shifts under an AMOC shutdown, is suggested as a future research priority. Abstract : The seasonal response of rainfall over tropical South America to a collapse in the Atlantic Meridional Overturning Circulation (AMOC) is examined. The large seasonal variation in rainfall response is linked with the seasonal migration in peak rainfall (driven by variation in solar insolation and Atlantic sea surface temperatures). The simulated rainfall changes appear to be biased in some months by the southward bias in the Atlantic Intertropical Convergence Zone (ITCZ), including a possible overestimation of drying in March and June.